Listening in the dark: why we need stories of people living with severe and enduring anorexia nervosa. Issue 1 (December 2016) - Conti, Janet; Rhodes, Paul; Adams, Heather
Abstract A bold step forward in our approach to Severe and Enduring Anorexia Nervosa invites new paradigms for research and practice. It provides an opportunity for us to explore fault lines, both in our communities of practice and the social structures that inform them. This paper serves to question the medical metaphors on which treatment has been based, in favour of alternative perspectives that resonate more clearly with the lived experience of those for whom it has failed. We invite the consideration of alternative metaphors, which can disrupt the notion of heroic patients (and therapists), mediate against acts of self-silencing and sensitising us to more radical acts of listening. Beyond the randomised trials and manuals it is time for us to listen to the realities of suffering, the minutiae of resistance and the life that can still be lived.